Human papillomavirus (HPV) genotypes associated with laryngeal papilloma. Issue 3 (March 1988) - Corbitt, G; Zarod, A P; Arrand, J R; Longson, M; Farrington, W T
Abstract : Biopsy specimens from 14 patients treated for laryngeal papillomatosis were tested for the presence of human papillomavirus (HPV) genome by the technique of DNA-DNA hybridisation. According to the age of initial presentation, cases were subdivided into juvenile (less than 16 years) and adult onset (older than 16 years) groups. Histological investigation confirmed that it was impossible to distinguish the groups on this basis. Molecular virology using both dot blot and Southern transfer techniques showed that 10 cases carried the HPV type 6 genome, three cases HPV type 11, and in one case no HPV DNA was detected. All six adult onset cases carried HPV 6 sequences while the juvenile onset group comprised four HPV 6 and three HPV 11 cases. In the juvenile onset group more females were affected; in the adult onset group more males were affected. Two of the patients shown to have HPV type 11 sequences in their biopsy material were the most resistant to treatment. One of the adult onset cases subsequently developed a squamous cell carcinoma of the larynx in which HPV 6 DNA was detected. As far as we know this is first time that HPV-DNA has been confirmed in laryngeal papilloma undergoing malignant change.